2019
DOI: 10.1186/s12920-019-0481-z
|View full text |Cite
|
Sign up to set email alerts
|

Exome, transcriptome and miRNA analysis don’t reveal any molecular markers of TKI efficacy in primary CML patients

Abstract: BackgroundApproximately 5–20% of chronic myeloid leukemia (CML) patients demonstrate primary resistance or intolerance to imatinib. None of the existing predictive scores gives a good prognosis of TKI efficacy. Gene polymorphisms, expression and microRNAs are known to be involved in the pathogenesis of TKI resistance in CML. The aim of our study is to find new molecular markers of TKI therapy efficacy in CML patients.MethodsNewly diagnosed patients with Ph+ CML in chronic phase were included in this study. Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…Jurkovicova et al found a total of 70 differentially expressed miRNAs between treatment-naïve non-responders and responders, José-Enériz et al identified 19 miRNAs and Mosakhani et al detected only one miRNA, miR-181c-5p, to be significantly down-regulated in non-responders compared to responders [9][10][11]. Furthermore, Lavrov et al did not find any miRNA, whose expression pattern could discriminate between non-responds and responds to TKI therapy at time of diagnosis [12]. This inconsistency of study results might be based on factors such as differences in study design including diverse sample origin (peripheral blood or bone marrow), differences in patient cohorts, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Jurkovicova et al found a total of 70 differentially expressed miRNAs between treatment-naïve non-responders and responders, José-Enériz et al identified 19 miRNAs and Mosakhani et al detected only one miRNA, miR-181c-5p, to be significantly down-regulated in non-responders compared to responders [9][10][11]. Furthermore, Lavrov et al did not find any miRNA, whose expression pattern could discriminate between non-responds and responds to TKI therapy at time of diagnosis [12]. This inconsistency of study results might be based on factors such as differences in study design including diverse sample origin (peripheral blood or bone marrow), differences in patient cohorts, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As drug resistance still remains a challenge in CML treatment, predictive biomarkers would help to optimize patients’ therapy. MiRNAs are frequently discussed as potential candidates for these biomarkers [ 12 , 71 , 72 ]. So far, three out of the four studies analyzing miRNA expression pattern of treatment-naïve CML patients at time of diagnosis suggested selected miRNAs as potential predictive markers for TKI resistance [ 9 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations